Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/gbe/evaa167
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evolution and Structural Adaptation to the Deep Ocean in the Protein-Folding Chaperonin CCTα

Abstract: The deep ocean is the largest biome on Earth and yet it is among the least studied environments of our planet. Life at great depths requires several specific adaptations, however their molecular mechanisms remain understudied. We examined patterns of positive selection in 416 genes from four brittle star (Ophiuroidea) families displaying replicated events of deep-sea colonization (288 individuals from 216 species). We found consistent signatures of molecular convergence in functions related to protein biogenes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…Other variables, such as dissolved oxygen concentration, pH, temperature, and salinity, do not vary sufficiently within the depth and geographical range of the examined populations in the study area to exert any significant adaptive pressure that could drive diversification. Several studies have suggested that pressure can be a significant selective force in the deep sea, often driving the evolution of pressure-adapted enzymes and other biomolecules (Somero, 1992;Lan et al, 2017Lan et al, , 2018Gaither et al, 2018;Lemaire et al, 2018;Gan et al, 2020;Weber et al, 2020).…”
Section: Metapopulation Structuring By Depthmentioning
confidence: 99%
“…Other variables, such as dissolved oxygen concentration, pH, temperature, and salinity, do not vary sufficiently within the depth and geographical range of the examined populations in the study area to exert any significant adaptive pressure that could drive diversification. Several studies have suggested that pressure can be a significant selective force in the deep sea, often driving the evolution of pressure-adapted enzymes and other biomolecules (Somero, 1992;Lan et al, 2017Lan et al, , 2018Gaither et al, 2018;Lemaire et al, 2018;Gan et al, 2020;Weber et al, 2020).…”
Section: Metapopulation Structuring By Depthmentioning
confidence: 99%
“…In the three species studied, genes with a conserved pattern of promoter hypomethylation and gene body hypermethylation (conducive to upregulation) displayed strong methylation-driven mutational biases and were disproportionately associated with the maintenance of protein homeostasis. Chaperones, which are important for protein folding stability in the deep sea ( Cario et al 2016 ; Ritchie et al 2018 ; Weber et al 2020 ), were highly methylated in the worms. Likewise, the ubiquitin–proteasome pathway, which is responsible for degrading misfolded or damaged proteins and plays an important role in cold water–adapted species ( Todgham et al 2017 ), was overrepresented amongst genes with hypomethylated promoters in all three worms.…”
Section: Discussionmentioning
confidence: 99%
“…To detect positively selected genes, species with specific traits, i.e. Crabtree effect and heat tolerance, and monophyletic groups of the related species (nodes) (Weber et al , 2020) were labelled as the “Foreground” in each gene tree, while the remaining were labelled as the “Background”. The gene tree approach is used in this work as only a subset of OGs have at least one corresponding sequence for each of the species from the species tree.…”
Section: Methodsmentioning
confidence: 99%